Goals of sustainable real estate development – a systematic literature review - Meinen, Heiko; Franz, Martin (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
Certification systems use concrete criteria to make sustainable building tangible. However, when it comes to the individual context, the initial question to clarify is which goals for sustainable project development are fundamentally applicable. Together with stakeholders, politics can then make prioritizations and develop targeted regulatory measures. Thus far, there is no comprehensive catalog of goals for real estate project development that the parties involved can work with. This paper presents the results of a systematic literature review on sustainability requirements in the fields of real estate geography, spatial planning, real estate economics, architecture, and civil engineering, and derives goal formulations for sustainable real estate project development. Approximately 150 sources were analyzed, identified using relevant international literature databases and other public information. It becomes evident that aspects from the various scientific fields do overlap, but essentially complement each other, resulting in a comprehensive target profile for project development. The findings serve as a starting point for further research on complexity management and the support of sustainable development in the real estate sector.